Friction stir welding : from basics to applications - Lohwasser, Daniela; Chen, Zhan (Woodhead Publishing in materials., 2010)
Friction stir welding (FSW) is a highly important and recently developed joining technology that produces a solid phase bond. It uses a rotating tool to generate frictional heat that causes material of the components to be welded to soften without reaching the melting point and allows the tool to move along the weld line. Plasticized material is transferred from the leading edge to trailing edge of the tool probe, leaving a solid phase bond between the two parts. Friction stir welding: from basics to applications reviews the fundamentals of the process and how it is used in industrial applicat.